Legal Protection for Notaries from Crimes of Misbruik Van Omstandigheden in Making Dependency Deeds - Noor, Aslan; Suprapto, Lusi Apriyanti; Abyansyah, Aditya Fadil; Fauzi, Fauzan Muhamad (International Journal of Science and Society, 2024)
In carrying out their duties, notaries often face situations where interested parties try to manipulate the situation in order to gain illegal benefits, which can have legal implications for the validity of the deed made. This research aims to examine legal protection for notaries in dealing with the crime of misbruik van omstandigheden (abuse of circumstances) in making a mortgage deed. This research uses a normative juridical method with a statutory approach to analyze existing legal protection and the effectiveness of its implementation. The findings reveal that Mortgage Rights under Indonesian civil law serve to ensure debt repayment and offer security to creditors. In case of debtor default, creditors can enforce these rights through a public auction in line with UUHT regulations. Authentic deed validity relies on both formal (technical and procedural) and material (agreement substance) aspects. Misuse of circumstances, where one party exploits the other's vulnerability for unfair gain, can lead to agreement annulment. Legal safeguards for notaries are outlined in Law No. 30/2004 and Law No. 2/2014, encompassing evidence generation, users, and notaries' roles as public officials. Oversight by the Notary Honorary Council (MKN) ensures compliance with duties, imposes sanctions for violations, and governs document summoning procedures. The notary's right of recusal upholds document confidentiality and integrity, while administrative sanctions uphold professional conduct. Minister of Law and Human Rights Regulation No. 7/2016 emphasizes transparent and rule-compliant notary summoning procedures, enabling notaries to fulfill their duties securely and calmly while balancing legal scrutiny with notary rights protection.